Liver Steatosis: Better Predictor of CKD in MAFLD Than Liver Fibrosis as Determined by Transient Elastography With Controlled Attenuation Parameter - Marc, Luciana; Mihaescu, Adelina; Lupusoru, Raluca; Grosu, Iulia; Gadalean, Florica; Bob, Flaviu; Chisavu, Lazar; Olariu, Nicu; Tucicovschi, Vlad; Timar, Bogdan; Sporea, Ioan; Timar, Romulus; et al. (Frontiers in Medicine, 2022)
Background: Changing the term/concept of the non-alcoholic fatty liver disease (NAFLD) to metabolic dysfunction associated fatty liver disease (MAFLD) may broaden the pathological definition that can include chronic renal involvement, and, possibly, changes chronic kidney disease's (CKD's) epidemiological association with liver disease, because CKD is associated with metabolic disorders and almost all patients with CKD present some form of an atherogenic dyslipidemia. Our study explores the relationship between MAFLD and CKD using Transient Elastography (TE) with a Controlled Attenuated Parameter (CAP). Methods: We evaluated 335 patients with diabetes with MAFLD and with high CKD risk using TE with CAP (FibroScan®). The CKD was defined according to Kidney Disease Improving Global Outcomes (KDIGO) 2012 guidelines. Logistic regression and stepwise multiple logistic regression were used to evaluate the factors associated with CKD. In addition, a receiver operating characteristic curve (ROC) analysis was used to assess the performance of CAP and TE in predicting CKD and its optimal threshold. Results: The prevalence of CKD in our group was 60.8%. Patients with CKD had higher mean liver stiffness measurements (LSM) and CAP values than those without CKD. We found that hepatic steatosis was a better predictor of CKD than fibrosis. Univariate regression showed that CAP values >353 dB/m were predictive of CKD; while the multivariate regression analysis (after adjustment according to sex, body mass index (BMI), low-density lipoprotein cholesterol (LDLc), and high-density lipoprotein cholesterol (HDLc), and fasting glucose) showed that CAP values >353 dB/m were more strongly associated with the presence of CKD compared to the LSM (fibrosis) values. Conclusion: In patients with MAFLD, CAP-assessed steatosis appears to be a better predictor of CKD compared to LSM-assessed hepatic fibrosis.